Improvement of brain perfusion in patients with chronic brain ischemia at epidural spinal cord electrical stimulation - Zhao, Shu; Sufianova, Galina; Shapkin, Andrey; Mashkin, Andrey; Meshcheryakova, Svetlana; Han, Dayong (Frontiers in Surgery, 2022)
Objective The aim of this study was to study changes in the cerebral circulation in patients with neuropathic pain syndromes with concomitant chronic cerebral ischemia against the background of test and prolonged epidural electrical stimulation of the spinal cord. Results All patients of the main clinical group on the background of electrical stimulation subjectively described an improvement in well-being, normalization of sleep and a decrease in the level of anxiety and depression, cognitive functions. According to the visual 10-point analog scale, the intensity of pain syndrome on the background of electrical stimulation decreased in subgroup 1 from 6.6±0.19 to 2.5±0.1 (p≤0.01) on day 5 and 1.8±0.2 score after 1 year (p≤0.01). In the second subgroup, the intensity of the pain syndrome decreased from 6.7±0.2 to 2.5±0.2 (p≤0.01) on day 5 and 1.9±0.2 points after 1 year (p≤0, 01). In the control group, in all patients, the level of pain syndrome decreased in the postoperative period from 6.4±0.2 to 1.6±0.18 (p≤0.01) on day 5. At the follow-up examination, almost all patients of this group experienced recurrence of pain syndrome, which averaged 4.3±0.3 in the group (p≤0.01 compared with the initial level). An increase in the intensity of the pain syndrome by more than 3 points was observed in 62.5% of patients. The change in local cerebral blood flow in patients of the control group in all periods was not statistically significant. In all patients of the main group, both with stimulation of the lower thoracic and cervical sections of the spinal cord, an improvement in cerebral circulation was noted according to CT perfusion of the brain. There was no significant correlation between the severity of pain reduction and improvement in brain perfusion. Conclusion The “functional” cerebral revascularization observed by us in chronic ischemia in the elderly seems promising as a new direction in functional neurosurgery in cerebrovascular diseases.